2008
DOI: 10.1039/b719205c
|View full text |Cite
|
Sign up to set email alerts
|

Study on a set of bis-cyclometalated Ir(iii) complexes with a common ancillary ligand

Abstract: Bis-cyclometalated iridium(III) complexes [Ir(F2ppy)2ZN] (FZN), [Ir(F2CNppy)2ZN] (FCZN), [Ir(DMAF2ppy)2ZN] (FDZN) and [Ir(MeOF2ppy)2ZN] (MeOFZN) (F2ppy = 4',6'-difluoro-2-phenylpyridinate, F2CNppy = 5-cyano-4',6'-difluoro-2-phenylpyridinate, DMAF2ppy = 4',6'-difluoro-4-dimethylamino-2-phenylpyridinate, MeOF2ppy = 4',6'-difluoro-4-methyl-2-phenylpyridinate and ZN = 3,5-dimethylpyrazole-N-carboxamide) emitting in the sky blue region were synthesized. We studied the effect of the ancillary ligand ZN and the subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 74 publications
1
15
0
Order By: Relevance
“…A typical procedure involves a prior preparation of the chloride-bridged dimers with formula [(C 4 N) 2 Ir(m-Cl)] 2 , followed by conversion to the anticipated heteroleptic complexes by replacing the chlorides with other easily accessible L 4 X ancillary chelates (L 4 X is a bidentate chelate constructed from a neutral L and an anionic X entity), such as acetylacetonate (acac), functionalized b-diketonate, N-methylsalicylimine (sal) or picolinate (pic). 10,45 Many of the heteroleptic complexes [Ir(C 4 N) 2 (L 4 X)] are known to exhibit room-temperature phosphorescence similar to those of the tris-cyclometalated complexes, leading to the conclusion that the luminescence is mainly controlled by the common [Ir(C 4 N) 2 ] fragment, while the emission wavelength is strongly dependent on the choice of C 4 N cyclometalating ligands; that is, a more extended electron delocalization would exhibit red-shifting of emission wavelengths. Such a generalized observation then provides a practical advantage, since the related homoleptic (i.e.…”
Section: Ir(iii) Complexesmentioning
confidence: 99%
“…A typical procedure involves a prior preparation of the chloride-bridged dimers with formula [(C 4 N) 2 Ir(m-Cl)] 2 , followed by conversion to the anticipated heteroleptic complexes by replacing the chlorides with other easily accessible L 4 X ancillary chelates (L 4 X is a bidentate chelate constructed from a neutral L and an anionic X entity), such as acetylacetonate (acac), functionalized b-diketonate, N-methylsalicylimine (sal) or picolinate (pic). 10,45 Many of the heteroleptic complexes [Ir(C 4 N) 2 (L 4 X)] are known to exhibit room-temperature phosphorescence similar to those of the tris-cyclometalated complexes, leading to the conclusion that the luminescence is mainly controlled by the common [Ir(C 4 N) 2 ] fragment, while the emission wavelength is strongly dependent on the choice of C 4 N cyclometalating ligands; that is, a more extended electron delocalization would exhibit red-shifting of emission wavelengths. Such a generalized observation then provides a practical advantage, since the related homoleptic (i.e.…”
Section: Ir(iii) Complexesmentioning
confidence: 99%
“…The filtrate was concentrated on a rotavap to give a crude product, which was then purified by silica gel column chromatography using a 1 : 1 mixture of ethyl acetate and hexane as eluent. Finally, the yellow crystals were crystallized from a mixture of CH 2 Cl 2 and hexane at RT (4,31 (d, J = 8.5 Hz, 1H), 6.79 (t, J = 9.0 Hz, 2H), 6.73 (t, J = 7.0 Hz, 1H), 6.66 (t, J = 8.0 Hz, 1H), 6.38 (td, J = 7.5, 2.5 Hz, 2H), 6.12 (d, J = 7.0 Hz, 1H), 5.87 (t, J = 10.0 Hz, 2H), 1.59 (s, 3H N,3.20;C,60.33;H,3.80. Found: N,2.94;C,60.48;H,4.11. Synthesis of [Ir(dpna) 2 (fppz)] (5a and 5b) from 2.…”
Section: Synthesis Of [Ir(dppi) 2 (Oac)] (4)mentioning
confidence: 99%
“…This can lead to a local electric field, which can induce the charges, thus facilitating charge injection into the dopant. 36 This results in the hole and electron trapping balance in Eu-DDPz, and this may be another reason leading to the pure 612 nm emission. While for Eu-PyPhen and Eu-MPP, at higher relative applied voltage, holes can be firstly injected into the HOMO of dopants, and then electrons can be injected into the CBP layer, because it has been demonstrated that holes are the majority carrier in EML due to the lower energy barrier of hole injection into the EML than electron.…”
Section: El Efficiency Comparison In Oledsmentioning
confidence: 99%